Model of Agricultural Land Use Change and Effects on Social Economy Condition of Local in East Lombok Regency - Nugroho, Cahyadi (Sumatra Journal of Disaster, Geography and Geography Education, 2017)
The purpose in this research to discuss about the change of agricultural land, social economy condition of local in East Lombok Regency, and the planning model of land conversion to social economy of local in East Lombok Regency. The type of research in this study used applied research. Data analysis used GIS analysis method through ArcGIS software to get the change of agricultural land use into built up area in East Lombok Regency, social economy condition through statistic analysis and modeling through ISM analysis. The results of the research are: 1) The conversion of agricultural land into built up area in East Lombok Regency from 2012 until 2015 increases the extent which commonly used local for tobacco plantations; 2) the social economy condition of local in East Lombok Regency, in terms of profession, most of the people are farmers, traders and services, in economy productivity of East Lombok Regency derived from agricultural products and services, East Lombok local income most of them who work as agricultural laborers and service workers have a low income because not landowners or services. 3) social economy planning model based on land use change in East Lombok is to empower communities based on the potential of each sub-district by optimizing agricultural tourism, cultural tourism, integrated CBD through the role of government and local in land use which managed by local and supported by infrastructure, tourism promotion, and government regulations.